Pengembangan Mutu Sekolah Melalui Penerapan Ekstrakurikuler Berbasis Pendidikan Karakter Di Smp Kota Sragen - Nirwati, Nirwati; Supriyanto, Eko; Maksum, Muh. Nur Rochim; Mustofa, Triono Ali; Ramdhani, Deddy (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research is purpose to describe a model for developing school quality through the implementation of character education-based extracurricular at Birrul Walidain’s Muhammadiyah Middle School and Integrated Islamic Junior High School’s Az-Zahro Sragen. The type of this research used Field Research, with a qualitative approach. The object of this research are Birrul walidain’s Muhammadiyah Middle School and Integrated Islamic Junior High School’s Az-Zahro Sragen. The subject of this research include the Headmaster, vise principal of student affairs, extracurricular coordinator and students. Data collection techniques were carried out by observation, interviews and documentation. Data validity using triangulation. Data analysis was carried out in a qualitative descriptive manner.The result of the study show that the implementation of improving school quality through the implementation of character education-based extracurricular is carried out in the following steps (1) Making continuous improvement. School always make continuous improvement to unsure that all component of education providers can realize the vision, mission and goals of the school. (2) Setting quality standards. The intended quality standard is to determine the quality assurance of student’s character. Ownership of these character becomes specifications for student’s graduation which consists of object, aspect, and assessment instrument. (3) Carrying out cultural changes. The purpose of this concept is to form a school culture that respect quality as the orientation of all school stakeholder. (4) Changing the organization. This change concern the duties and authorities and responsibilities of teachers carried out through a decentralized approach. (5) maintaining good relations with customers to obtain customer satisfaction.The goal of extracurricular in character education is to integrated extracurricular materials with the noble values of the nation so it can be internalized into behavior that is manifested in student’s daily activities so it can become a habit. Keyword:education quality, extracurricular, and character education.